The interplay of job embeddedness, collective efficacy, and work meaningfulness on teacher well-being: a mixed-methods study with digital ethnography in China - Yumei Lei (Frontiers in Psychology, 2024)
IntroductionThis study examines the influence of teacher job embeddedness, collective efficacy, and work meaningfulness on the psychological well-being of Chinese teachers. The focus is on understanding how these constructs contribute to teacher well-being through a mixed-methods approach.MethodsA two-stage structural equation modeling (SEM) analysis was conducted using quantitative data collected from 406 in-service Chinese teachers. The study also incorporated a qualitative phase involving digital ethnography within online teaching communities to provide deeper insights into teachers’ experiences.ResultsThe quantitative analysis revealed significant positive direct effects of job embeddedness, collective efficacy, and work meaningfulness on psychological well-being, with work meaningfulness showing the strongest effect. The mediating role of work meaningfulness partially explained the relationships between job embeddedness, collective efficacy, and teacher well-being. The qualitative findings supported and expanded upon these results, emphasizing the role of a supportive school community and strong administrative leadership.DiscussionThe results suggest that enhancing job embeddedness, collective efficacy, and work meaningfulness can significantly contribute to teachers’ psychological well-being. These findings provide actionable insights for school leaders and policymakers in the Chinese educational system to foster environments that promote teacher well-being.